The Melt Enthalpy of Pu6Fe - Joshua D. Coe; William W. Anderson; Paul H. Tobash (Applied Sciences, 2021)
Schwartz, et al., previously reported calorimetry measurements conducted on a Pu-Pu<semantics>6</semantics>Fe mixture, from which they derived a melt enthalpy of 31.2 J/g (46.6 kJ/mol) for Pu<semantics>6</semantics>Fe. This was the first—and remains the only—such value to appear in the literature. We reanalyze those results in light of two contributions to the measured heat flow not considered in the original report: the melt enthalpy of the excess Pu and the subsequent heating of the liquid mixture. These corrections yield a revised value of 24.4 J/g (36.3 kJ/mol), which we show to be consistent with the melt enthalpy of U<semantics>6</semantics>Fe.